Strategic Readiness for Implementing Sustainable Marketing Practices: A Case Study of Total Energies in the Iraq Gas Project - Al-Thabit, Ahmed Sameer N.; Ahmed, Anmar Shihab; Nsaif, Murtadha Abdul Ghafoor (Indonesian Journal of Law and Economics Review, 2025)
General Background: Amid global environmental transformation, the oil and gas sector faces growing pressure to integrate sustainability into its operations and marketing functions. Specific Background: Total Energies’ gas project in southern Iraq offers a complex industrial and institutional environment in which sustainable marketing adoption reflects both corporate commitment and contextual constraints. Knowledge Gap: Despite the company’s declared sustainability vision, little empirical evidence exists on its actual strategic readiness to implement sustainable marketing practices within Iraq’s fragile institutional setting. Aims: This study investigates TotalEnergies’ strategic readiness across four dimensions—institutional leadership, organizational culture, resource availability, and environmental commitment and governance—to determine its capacity for adopting sustainable marketing.Results: Using a descriptive-analytical approach with 47 valid survey responses, findings reveal that leadership scored highest, mean = 4.08, followed by organizational culture, 3.58, and resources, 3.02, while environmental governance was weakest, 2.50, indicating major structural deficiencies. Novelty: The study uniquely applies the strategic readiness framework to an international energy company operating in Iraq’s gas industry, transforming theoretical constructs into measurable field indicators. Implications: The results highlight the need for enhanced environmental governance policies, capacity building, and institutional integration to translate sustainability rhetoric into operational practice and to guide similar corporations toward effective sustainable marketing implementation in challenging contexts.  Highlights: Leadership shows strong commitment but lacks systemic support. Environmental governance remains the weakest readiness factor. The study bridges theory and field application in Iraq’s gas industry. Keywords: Strategic Readiness, Sustainable Marketing, Environmental Governance, Organizational Culture, Total Energies